PENGARUH INFEKSI Escherichia coli BERBAGAI RUTE TERHADAP GAMBARAN HETEROFIL DAN TOTAL PROTEIN PLASMA (TPP) AYAM BROILER - , EKA WULANDARI, Dr. Drh. Bambang Sutrisno, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research conducted using the grower from day old chick (DOC) being kept open enclosure system with its own,18 chickens which is divided into six groups, each group of 3 chickens. Before infection, the sixth group of chicken blood samples taken each of as many as 2 - 3 cc for use as an overview of blood before treatment in order to compare with the blood samples after infection of Escherichia coli. The first group of chickens is not given any treatment, referred to as the control group. The second group was given chicken Eschericia coli infection through the cloacal route. The third group of chicken infection via the oral route. The fourth group of chicken infection via the intramuscular route. The fifth group of chicken infection through intravenous route. The sixth group of chickens and infect via the intratracheal. Then the sixth group of the treatment given infection Eschericia coli isolates, laboratory of Microbiology FKH UGM through various routes of infection with 1 cc volume and dose 108 CFU. After chicken left in less than 14 days with a given feeding, drinking, and enough vitamins, as well as in normal room temperature that is approximately 27 ï°C. After 14 days post infection blood sampling carried out on all the Group's treatment and the control group. Each chicken taken blood samples as much as 2 - 3 cc of blood. Examination of blood samples carried out in the laboratory of Clinical Pathology. Results of examination of blood samples of chickens completed with multifactorial statistical analysis (ANOVA 2 directions). Heterophile data shows there is no interaction between the factors of the path or route of infection and treatment (before, after) at the level of significance of 5% and increased levels of heterophile is highest on the intravenous group.Whereas in representations total plasma protein (TPP) indicates there are interactions between the factors of the infection with treatment (before, after) at the level of significance of 5% and increased levels of total plasma protein (TPP) exists on the intravenous group.